Genome mining of the Streptomyces avermitilis genome and development of genome-minimized hosts for heterologous expression of biosynthetic gene clusters. (1st February 2014) - Ikeda, Haruo; Shin-ya, Kazuo; Omura, Satoshi
Abstract: To date, several actinomycete genomes have been completed and annotated. Among them, Streptomyces microorganisms are of major pharmaceutical interest because they are a rich source of numerous secondary metabolites. S. avermitilis is an industrial microorganism used for the production of an anthelmintic agent, avermectin, which is a commercially important antiparasitic agent in human and veterinary medicine, and agricultural pesticides. Genome analysis of S. avermitilis provides significant information for not only industrial applications but also understanding the features of this genus. On genome mining of S. avermitilis, the microorganism has been found to harbor at least 38 secondary metabolic gene clusters and 46 insertion sequence (IS)-like sequences on the genome, which have not been searched so far. A significant use of the genome data of Streptomyces microorganisms is the construction of a versatile host for heterologous expression of exogenous biosynthetic gene clusters by genetic engineering. Since S. avermitilis is used as an industrial microorganism, the microorganism is already optimized for the efficient supply of primary metabolic precursors and biochemical energy to support multistep biosynthesis. The feasibility of large-deletion mutants of S. avermitilis has been confirmed by heterologous expression of more than 20 exogenous biosynthetic gene clusters.